The Development of Learning Model Through Problem Based Introduction (PBI) on Student’s Motivation Improvement in Mathematics Education - Dachi, Surya Wisada; Batubara, Ismail Hanif (International Journal for Educational and Vocational Studies, 2020)
The formulations of the study conclude into two aspects, that are: (1) How effective problem-based introduction (PBI) model for mathematics education students' motivation FKIP UMSU; (2) Does the learning model through Problem-Based Introduction provides a significant improvement on students' motivation. The objectives of this study were: (1) To determine the effectiveness of the problem-based introduction (PBI) model on mathematics education students' motivation in FKIP UMSU, (2) To increase the motivation for mathematics education students to FKIP UMSU through a problem-based introduction (PBI) model. From the results of the research carried out by developing a learning device based on a problem-based introduction (PBI) model to improve the learning motivation of mathematics education students at FKIP UMSU. From the hypothesis calculation data obtained t count > t table is 4,803 > 2,005 so that Ho rejected and Ha is accepted.